Effects of synthesis parameters on size of double-walled particles - Lim, Alvin Wei Yang. (2010)
Double-walled microspheres of Poly (L-lactic acid) (PLLA) and Poly (D, L-lactic-co-glycolic acid 50:50) (PLGA) were fabricated using the one-step solvent evaporation method. In this study, different process parameters affecting the particle size of microspheres were investigated. The morphologies and configurations of the microspheres were determined using the scanning electron microscope and polymer dissolution test using Tetrahydrofuran (THF). It was found that an increase in stirring speed resulted in a decrease in particle size of double-walled microspheres without changing the configuration. Increased starting polymer solution concentration resulted in an increase in particle size of microspheres, which to a certain extent do not produce double-walled microspheres due to high viscosity of polymer solution. It was also observed that lowering polymer solution concentration below cloud point or increased PVA solution concentration would result in smaller particles but increased the precipitation rate and produced microspheres without double-walled structure. In addition, it was proven that increasing the precipitation rate and amount of PLGA while decreasing oil to water ratio would create a kinetically favoured system, resulting in microspheres with core-shell inversion. A study on the effects of various process parameters were carried out on these microspheres. By varying the stirring speed, a range of various particle sizes of microspheres with core-shell inversion can be fabricated. Microspheres with core-shell inversion of larger size could be fabricated with increasing polymer solution concentration, while lower polymer concentration at cloud point resulted in small double-walled microspheres without the inversion. A further decrease in particle size of double-walled microspheres can be fabricated by using high stirring speed and PVA solution concentration due to the higher amount of PLGA.